2020
DOI: 10.1016/j.htct.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary diagnostics of chronic lymphocytic leukemia: European Research Initiative on CLL - ERIC recommendations

Abstract: Recent advances in chronic lymphocytic leukemia (CLL) includes description of disease genomic landscape, inclusion of prognostic relevant genetic tests in CLL workflow and evaluation of minimal residual disease (MRD) 1 in parallel with the increase availability of novel therapy agents. In this review, the theoretical and practical aspects of response assessment have been discussed. These are based on updated recommendations of the European Research Initiative on Chronic Lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…6 k). Several genetic alterations detected by FISH are prevalent among CLL patients, reflecting varying degrees of association with disease prognosis [ 43 ]. The presence of one or two C alleles was more common within the group of patients with chromosomal alterations determined by FISH than those with no alterations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 k). Several genetic alterations detected by FISH are prevalent among CLL patients, reflecting varying degrees of association with disease prognosis [ 43 ]. The presence of one or two C alleles was more common within the group of patients with chromosomal alterations determined by FISH than those with no alterations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 4 , 24 Using this approach in chronic lymphocytic leukemia, it was demonstrated that an MRD threshold of 0.01% (10 -4 ) was an independent predictor of progression-free survival in patients treated with either chemo-immunotherapy or novel agents. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Currently, the inclusion of TL evaluation in the proposed algorithm may be considered problematic as TL analysis has not yet been subjected to international standardisation. However, if a biomarker is deemed useful enough, then the requisite validation and standardisation will be performed as exemplified by the international effort to standardise IGHV mutation analysis, as well as TP53 mutations [11,12]. As part of the effort to develop a robust, reliable and accurate TL assay, suitable for clinical applications, high-throughput STELA was developed; this assay circumvents the labour intensive and technical issues of the original single molecule STELA assay and it has been already successfully employed for the evaluation of large numbers of clinical samples [13].…”
Section: To the Editormentioning
confidence: 99%